Identification of specific amino acid residues in the border disease virus glycoprotein E2 that modify virus growth in pig cells but not in sheep cells. (28th November 2020) - Fahnøe, Ulrik; Deng, Yu; Davids, Nana A.; Lohse, Louise; Bukh, Jens; Belsham, Graham J.; Rasmussen, Thomas Bruun
Abstract : Border disease virus (BDV) envelope glycoprotein E2 is required for entry into cells and is a determinant of host tropism for sheep and pig cells. Here, we describe adaptive changes in the BDV E2 protein that modify virus replication in pig cells. To achieve this, two BDV isolates, initially collected from a pig and a sheep on the same farm, were passaged in primary sheep and pig cells in parallel with a rescued variant of the pig virus derived from a cloned full-length BDV cDNA. The pig isolate and the rescued virus shared the same amino acid sequence, but the sheep isolate differed at ten residues, including two substitutions in E2 (K771E and Y925H). During serial passage in cells, the viruses displayed clear selectivity for growth in sheep cells; only the cDNA-derived virus adapted to grow in pig cells. Sequencing revealed an amino acid substitution (Q739R) in the E2 domain DA of this rescued virus. Adaptation at the same residue (Q739K/Q739R) was also observed after passaging of the pig isolate in sheep cells. Use of reverse genetics confirmed that changing residue Q739 to R or K (each positively charged) was sufficient to achieve adaptation to pig cells. Furthermore, this change in host tropism was suppressed if Q739R was combined with K771E. Another substitution (Q728R), conferring an additional positive charge, acquired during passaging, restored the growth of the Q739R/K771E variant. Overall, this study provided evidence that specific, positively charged, residues in the E2 domain DA are crucial for pig-cell tropism of BDV.